WHICH FANS ARE THE BIGGEST ACCELERATION OF THE GRANDSTAND? - Martin Verner (Acta Polytechnica CTU Proceedings, 2018)
The fans of AC Sparta Prague and SK Slavie Prague have been arguing about the fact whose fans support their team better since the end of 20th century. There have been made many experiments on the intensity of vibrations at football stadiums during matches. Altogether 11 matches were watched. Frequencies caused by the fans leadinng to vibrations and the size of those vibrations were provided from the results. Based on those facts the question about the bigger intensity of fans' support was answered.